2015
DOI: 10.1111/1462-2920.12942
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial sensing underlies artificial sweetener‐induced growth of gut Lactobacillus

Abstract: Disruption in stable establishment of commensal gut microbiota by early weaning is an important factor in susceptibility of young animals to enteric disorders. The artificial sweetener SUCRAM [consisting of neohesperidin dihydrochalcone (NHDC) and saccharin] included in piglets' feed reduces incidence of enteric disease. Pyrosequencing of pig caecal 16S rRNA gene amplicons identified 25 major families encompassing seven bacterial classes with Bacteroidia, Clostridia and Bacilli dominating the microbiota. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 40 publications
(54 reference statements)
1
33
0
Order By: Relevance
“…The supplementation of the diet with the artificial sweetener SUCRAM had a marked effect on the composition of the mucosa‐associated microbiota along the entire length of the intestinal tract, emphasising the conclusion made by Daly et al . () that supplementation of the diet with SUCRAM has a major influence on bacterial community structure in the pig intestine. Indeed, the significant increase in probiotic Lactobacillaceae population abundance reported by Daly et al .…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The supplementation of the diet with the artificial sweetener SUCRAM had a marked effect on the composition of the mucosa‐associated microbiota along the entire length of the intestinal tract, emphasising the conclusion made by Daly et al . () that supplementation of the diet with SUCRAM has a major influence on bacterial community structure in the pig intestine. Indeed, the significant increase in probiotic Lactobacillaceae population abundance reported by Daly et al .…”
Section: Discussionsupporting
confidence: 76%
“…To investigate the community structure and diversity of pig intestinal mucosa‐associated microbiota, DNA was extracted from mucosal scrapings taken from duodenum, jejunum, ileum, caecum, proximal colon and distal colon of 28‐day‐old piglets weaned to a defined basal diet (BD) and maintained on this diet for a period of 2 weeks (see Materials and methods for animals and Daly et al ., for dietary composition).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Positive prebiotic properties on tumors and ulcer as well as an immune stimulating and cholesterol-decreasing effect have been proved [35]. Studies showed that some Lactobacillus amylovorus strains isolated from pig fecal had a high tolerance to low pH and bile salts, with antimicrobial properties by bacteriocins and lactic acid production [7, 19]. Omar et al suggested that consuming L. amylovorus as a probiotic yoghurt has the capability to induce total body fat loss by decreasing gut microbial abundance of clostridia [25].…”
Section: Health Consequencesmentioning
confidence: 99%